HUBUNGAN KARAKTERISTIK IBU BERSALIN DENGAN TERJADINYA RETENSIO PLASENTA DI PUSKESMAS BABUSSALAM KECAMATAN BABUSSALAM KABUPATEN ACEH TENGGARA TAHUN 2021 - Fika Lestari; Purnama Sari Cane; Joharsah Joharsah (Jurnal Maternitas Kebidanan, 2021)
Causes and post partum bleeding include placental retention which reached 16%-17% in 2016. Placental retention is a condition in which the placenta is not born within 1 hour after the baby is born. The purpose of this study is to find out the relationship between maternal characteristics and the occurrence of placental retention in Babussalam Health Center in 2021. The research was conducted at Babussalam Health Center with a sample number of 22 people with this type of analytical survey research and cross sectional design. The results of the study can be seen with the Chi Square test with a confidence level of 95%, and a = 0.05, based on the parity it is known that X2 calculates > X2 table (14,157 > 7.815) then there is a relationship between parity and the occurrence of placental retention. Based on the age of daketahul X2 calculated > X2 table (13,093 > 5,991) then there is a relationship between the mother's age and the occurrence of placental retention. Based on the state of the uterus known X2 calculates > X2 table (10,092 > 3,841) then there is a relationship between the state of the mother's uterus and the occurrence of placental retention. Based on the sticking of the table is known X2 calculates > X2 table (9,322 > 5,991) it can be concluded that Ha was accepted and Ho was rejected. So there is a relationship between placental attachment and placental retention. There is a characteristic relationship of maternity mothers with the occurrence of placental retention. It is expected to the mother to keep her pregnancy distance and if the mother's age is > 35 years and already have more children and 3 should the mother not get pregnant again because it will be very risky to the mother and fetus.